The Houses of the Mosaics phase (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The central area of Nora contains rooms with mosaic floors which are overlain by walls of later epochs. Excavation from 2000 to 2005 revealed the stratigraphic relations between walls and surfaces, robbing trenches and plaster remains, floors, doorsteps etc. Phase plans have been assembled for at least two late 2nd -3rd century AD houses: the peristyle domus and the domus with mosaics south of the theatre. The first was decorated with mosaics featuring interlocking dodecahedra and circles, and meander patterns; those of  the second were more refined, one with wheels and rhombuses and another with concentric circles and shields and a central emblema.
Keywords: Nora; House; Mosaic; Peristyle; Phase Plan